Feeding on the smallest cells: an in situ study of picoplankton capture by bivalve molluscs from oligotrophic waters - Amit, Tal; Moskovich, Raz; Jacobi, Yuval; Shumway, Sandra E.; Ward, J. Evan; Beninger, Peter; Yahel, Gitai; Loya, Yossi (Frontiers in Marine Science, 2023)
Introduction Bivalve molluscs are among the most prominent coastal benthic-suspension-feeders and their farming is the largest and fastest-growing sector of aquaculture. More than a century of intensive laboratory studies (but surprisingly few in-situ studies) has yielded the consensus view that bivalves mainly capture particles >4µm. Nonetheless, bivalves thrive throughout the world’s oceans that are mostly oligotrophic, characterized by low food concentration and dominated by minute autotrophic picoplankton (<2 µm). Method We measured, in situ, the capture efficiency of naturally occurring planktonic cells by five suspension-feeding bivalve species from four families and three orders, residing in two oligotrophic basins: the Red Sea and the East Mediterranean Sea. Results Three species captured micron and submicron autotrophic cells with high efficiency (60-90%), suggesting a wider trophic niche than hitherto believed. In contrast, two sympatric species captured mainly particles >10 µm. Discussion These results suggest that the same basic anatomical tool kit, variably modulated according to taxa, habitat, or life history traits, enables the remarkable evolutionary and ecological success of bivalves in trophically-diverse habitats.